2015
DOI: 10.1002/cphc.201500062
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Long‐Range Photoinduced Electron Transfer through DNA by Hydroxyquinolines as Artificial Base Pairs

Abstract: The C-nucleoside based on the hydroxyquinoline ligand (Hq) is complementary to itself and forms stable Hq-Hq pairs in double-stranded DNA. These artificial Hq-Hq pairs may serve as artificial electron carriers for long-range photoinduced electron transfer in DNA, as elucidated by a combination of gel electrophoretic analysis of irradiated samples and time-resolved transient absorption spectroscopy. For this study, the Hq-Hq pair was combined with a DNA-based donor-acceptor system consisting of 6-N,N-dimethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…A photoexcitable dimethylaminopyrenyl donor attached to a deoxyuracil ( AP dU, E red *=−2.2 V vs. NHE) that exhibits suitable redox properties for long range charge transfer experiments was successfully used by Bätzner et al. to inject an electron in hydroquinoline base surrogates …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A photoexcitable dimethylaminopyrenyl donor attached to a deoxyuracil ( AP dU, E red *=−2.2 V vs. NHE) that exhibits suitable redox properties for long range charge transfer experiments was successfully used by Bätzner et al. to inject an electron in hydroquinoline base surrogates …”
Section: Figurementioning
confidence: 99%
“…to inject an electron in hydroquinoline base surrogates. [9] In this study, we investigated the EET through DNA containing phenanthrenyl base surrogates with different reduction potentials and LUMO energy levels. It is believed that the electron transfer within DNA can be modulated by the installation of a potential energy gradient.…”
mentioning
confidence: 99%
“…The structural stability of double helical DNA is primarily due π-electron stacking interactions between adjacent base pairs. It is this π-system that enables electron transfer (ET) throughout DNA [ 55 , 56 , 57 , 58 ]. Electrons migrate across charge carrying bases in a multistep hopping process, where the transfer rate is dependent on base separation [ 59 ].…”
Section: Electron Transfer Enhancement By Ruthenium-nucleic Acid Cmentioning
confidence: 99%
“…However, previous studies have shown, that oxidation of guanosine by DMAPylinked deoxynucleosides as the built-in electron donor is rather unlikely. [17] After irradiation of duplexes D0_ds, D2_ds and D3_ds, followed by enzymatic digestion and RP-HPLC analysis, reduction of the 5BrdU peak area in relation to the peak area of G is clearly visible, thus indicating debromination of 5BrdU and thereby confirming successful charge transfer. Moreover, as already seen in the fluorescence quenching assay, charge transfer occurs in a distance dependent manner, as Q 5BrdU/G is most significantly reduced for D0_ds, followed by D2_ds and D3_ds in relation to Dbr_ds (Figure 2 B).…”
mentioning
confidence: 94%